Biological dressing is a paradigm shift in children’s scald burn: our experience - Gupta, Madhusoodan; Varshney, Deepti (International Surgery Journal, 2021)
Background: Burn injury has multiple causes but scald burn is the most common type of burn in children. Prototype of scald burn is hot water burn. Change of burn dressing in children is challenging. Biological collagen dressing has totally changed the management of scald burn or it is a paradigm shift in the management of scald burn in children. Aim of this study was to achieve early wound healing with less complication and to prevent change of frequent dressings in children. Methods: A prospective study was done in 30 patients of scald burn under 12 years of age between November 2020 to July 2021. Meticulous debridement and deroofing of all blisters and removal of dead skin were performed. Bovine meshed wet collagen dressing was thoroughly rinsed with normal saline three times to remove the preservative isopropyl alcohol. After that collagen dressing applied over the raw area. Paraffin with chlorhexidine impregnated gauze dressing applied over the collagen. First dressing was changed at post operative day five. Results: All burn wounds healed well between 10-14 days without any complications. In follow up no hypertrophy of skin and almost same skin color had noted. Conclusions: We conclude that collagen dressing is a paradigm shift in the management of scald burn. It is cost effective, pain less, requires less frequent change of dressing with good match of skin color.